Cholesterol Efflux Pathways Suppress Inflammasome Activation, NETosis, and Atherogenesis. Issue 9 (28th August 2018) - Westerterp, Marit; Fotakis, Panagiotis; Ouimet, Mireille; Bochem, Andrea E.; Zhang, Hanrui; Molusky, Matthew M.; Wang, Wei; Abramowicz, Sandra; la Bastide-van Gemert, Sacha; Wang, Nan; Welch, Carrie L.; Reilly, Muredach P.; et al.
Abstract : Background: The CANTOS trial (Canakinumab Antiinflammatory Thrombosis Outcome Study) showed that antagonism of interleukin (IL)–1β reduces coronary heart disease in patients with a previous myocardial infarction and evidence of systemic inflammation, indicating that pathways required for IL-1β secretion increase cardiovascular risk. IL-1β and IL-18 are produced via the NLRP3 inflammasome in myeloid cells in response to cholesterol accumulation, but mechanisms linking NLRP3 inflammasome activation to atherogenesis are unclear. The cholesterol transporters ATP binding cassette A1 and G1 (ABCA1/G1) mediate cholesterol efflux to high-density lipoprotein, and Abca1/g1 deficiency in myeloid cells leads to cholesterol accumulation. Methods: To interrogate mechanisms connecting inflammasome activation with atherogenesis, we used mice with myeloid Abca1/g1 deficiency and concomitant deficiency of the inflammasome components Nlrp3 or Caspase-1/11 . Bone marrow from these mice was transplanted into Ldlr −/− recipients, which were fed a Western-type diet. Results: Myeloid Abca1/g1 deficiency increased plasma IL-18 levels in Ldlr −/− mice and induced IL-1β and IL-18 secretion in splenocytes, which was reversed by Nlrp3 or Caspase-1/11 deficiency, indicating activation of the NLRP3 inflammasome. Nlrp3 or Caspase-1/11 deficiency decreased atherosclerotic lesion size in myeloid Abca1/g1 -deficient Ldlr −/− mice. Myeloid Abca1/g1 deficiency enhanced caspase-1 cleavage not only in splenic monocytes and macrophages, but also in neutrophils, and dramatically enhanced neutrophil accumulation and neutrophil extracellular trap formation in atherosclerotic plaques, with reversal by Nlrp3 or Caspase-1/11 deficiency, suggesting that inflammasome activation promotes neutrophil recruitment and neutrophil extracellular trap formation in atherosclerotic plaques. These effects appeared to be indirectly mediated by systemic inflammation leading to activation and accumulation of neutrophils in plaques. Myeloid Abca1/g1 deficiency also activated the noncanonical inflammasome, causing increased susceptibility to lipopolysaccharide-induced mortality. Patients with Tangier disease, who carry loss-of-function mutations in ABCA1 and have increased myeloid cholesterol content, showed a marked increase in plasma IL-1β and IL-18 levels. Conclusions: Cholesterol accumulation in myeloid cells activates the NLRP3 inflammasome, which enhances neutrophil accumulation and neutrophil extracellular trap formation in atherosclerotic plaques. Patients with Tangier disease, who have increased myeloid cholesterol content, showed markers of inflammasome activation, suggesting human relevance. Abstract : Supplemental Digital Content is available in the text.